The New Fontana dictionary of modern thought - Bullock, Alan; Lawrie, Alf; Trombley, Stephen (HarperCollins Publishers, 1999)
A new, fully revised and updated edition of a well-established, unique work of reference and companion to all fields of modern thought. * First published in Fontana paperback in 1977; second revised edition published in Fontana paperback in 1988; now the third substantially revised edition makes its first ever appearance in hardback. * Edited by Alan Bullock (author of HITLER AND STALIN: Fontana Press) and Stephen Trombley, the book covers the whole range of modern thought, including: anthropology, world history, critical theory, economics, education, philosophy, music, cinema, drama, architecture, literature, medicine, law, geography, linguistics, criminology, feminism, sociology, archaeology, religion, maths, computer studies, psychology, the sciences...